Analisis Kelayakan Usahatani Ikan Asin Gabus ( Ophiocephalus Striatus ) Di Distrik Sota Kampung Sota - Ena, Hilarius R.M.; Untari, Untari; Widyantari, Ineke Nursih (MuJAgri: Musamus Journal of Agribusiness, 2021)
Cork salted fish farming is one of the leading commodities in Sota Village. The development of this business is still traditional and on a household scale. This study aims to analyze the feasibility of salted cork fish farming using Revenue Cost Ratio (R/C ratio) in Kampung Sota District, the study was conducted for one month, starting from April 2015 intil May 2015. Withdrawal of samples is made using total sampling defined deliberately and qualitative and quantitative methods do data analysis, this technique is used to high cost income levels and analyze business feasibility, such as the R/C ratio. The results showed that the average income of salted snakehead fish cultivation per season was 13,259,187.00. Cultivation of salted snakehead fish is worthy of a match in Kampung Sota District, the results from analysis of the feasibility analysis of salted snakehead fish cultivation obtain an R/C ratio value of 1.23.